2008
DOI: 10.1002/cncr.23531
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary management of colorectal brain metastases

Abstract: BACKGROUND.The incidence of brain metastases (BM) from colorectal cancer (CRC) is increasing, and the management of this previously rare complication at a single institution is reported.METHODS.The records of all patients with BM from 1994 to 2005 were reviewed, and 49 patients (33 men, 16 women) with 102 BM from CRC were identified. Associations between patient and tumor characteristics, treatment modality, and survival were assessed.RESULTS.The median age at diagnosis of BM from CRC was 66 years. Forty patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 32 publications
2
14
1
Order By: Relevance
“…In line with previous reports, the current series confirms that concomitant extracerebral metastases are a very common finding [10,11,12,13,14,15] and that the median age of the patients is 61–66 years [10,15,16,17,18]. The initial intention of the authors was to perform this analysis in the same way they evaluated time trends in the treatment of brain metastases from breast cancer [3].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In line with previous reports, the current series confirms that concomitant extracerebral metastases are a very common finding [10,11,12,13,14,15] and that the median age of the patients is 61–66 years [10,15,16,17,18]. The initial intention of the authors was to perform this analysis in the same way they evaluated time trends in the treatment of brain metastases from breast cancer [3].…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, it might be prudent to analyse the performance of the well-known prognostic scores, RPA and GPA, in patients with colorectal cancer brain metastases. Kruser et al [10] and Amichetti et al [14] did not confirm the prognostic impact of the RPA classes, while Fowler et al [17] and the present study did. As illustrated in figure 4, survival of patients with a poor performance status (RPA class III) is very limited.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Those originating from a colorectal primary are relatively rare, with a reported incidence ranging from 1% to 4% 9,10 study showed the 5-year cumulative incidence of brain metastases to be approximately 16%, 10%, 7%, and 5% for patients with lung cancer, renal cell cancer, melanoma, and breast cancer respectively; brain metastases accounted for fewer than 1% of metastases in crc 11 . Although brain metastases from crc are less common than those from malignant melanoma and lung and breast cancer, their effect on prognosis is equally serious 12 . Most brain metastases from solid tumours result from hematogenous spread rather than from dissemination via cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%